دراسة تأثير تغير حجم البيانات على أداء نظم إدارة قواعد البيانات السحابية والهجينة والتقليدية - ألفت جولحة; فاطمة أبوشامة (Tishreen University, 2016)
مع النمو المتسارع لحجم البيانات المخزنة في الأنظمة السحابية تصبح الحاجة إلى المعالجة الفعالة للبيانات أمراً حرجاً وملحاً. يقدم هذا البحث دراسة أهم خصائص نظم إدارة قواعد البيانات الآتية: Hive وSQLMR وMariaDB Galera. إن Hive هو نظام إدارة قواعد بيانات سحابي. وSQLMR هو نظام هجين يعتمد على الدمج بين قدرات النظم السحابية والتقليدية. أما Galera MariaDB فهو من نظم إدارة قواعد البيانات التقليدية المطورة لمواكبة الخصائص السحابية. تم في هذا البحث عرض أهم التطويرات التي تمت على تلك النظم ومقارنة أدائها في معالجة البيانات بالاعتماد على قياس زمن تنفيذ عمليات استعلام مع تغير حجم البيانات، وذلك من أجل التعرف على أداء تلك الأنظمة عملياً ومعرفة متطلبات تطويرها للوصول إلى نظام إدارة بيانات أمثلي، ولمساعدة المستخدمين في اختيار نظام قواعد البيانات الذي يحقق متطلباتهم من ناحية التوافرية والتدرجية. With the rapid growth of the size of the data stored in the cloud systems, the need for effective data processing becomes critical and urgent. This research introduces a study of the most important characteristics of databases management systems: Hive, SQLMR, and MariaDB Galera. Hive is a cloud database management system. SQLMR is a hybrid system, which depends on the integration between the cloud and traditional systems capabilities. While MariaDB Galera is a traditional database management system developed to cope with the cloud characteristics. In this research, we show the most important developments that have been on those systems, and then we compare their performance in data processing based on the execution time of query operations with the change of the volume of data. That is to identify the performance of those systems practically and to know the developing requirements for access to optimized data management system, and to help users in the selection of the database system that achieves their requirements in terms of availability and scalability.